2014
DOI: 10.1182/blood-2013-11-539742
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health care settings on survival time of patients with chronic myeloid leukemia

Abstract: Key Points CML patients enjoyed superior survival chances when treated in THs. Treatment centers having less experience with CML patients did not affect the patient’s survival chances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 6 publications
1
13
2
Order By: Relevance
“…54 All patients were treated with first-line imatinib, at an initial dose of 400 mg (76% of patients) or 800 mg (24% of patients). A significant proportion of the patients treated with 800 mg had a high Sokal score, and it was already reported that in these patients the dose of imatinib did not affect significantly the response.…”
Section: Discussionmentioning
confidence: 99%
“…54 All patients were treated with first-line imatinib, at an initial dose of 400 mg (76% of patients) or 800 mg (24% of patients). A significant proportion of the patients treated with 800 mg had a high Sokal score, and it was already reported that in these patients the dose of imatinib did not affect significantly the response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications suggested that centralised care of patients with CML is important for achieving results comparable with those of clinical trials [35,44]. More recently, Lauseker et al, analysing the outcome of 1491 patients included in the German CML Study IV, observed a survival advantage for patients treated initially at a teaching hospital compared to those treated in municipal hospitals and by officebased physicians, respectively [45].…”
Section: Survival Rates and Non-disease-related Prognostic Factorsmentioning
confidence: 99%
“…For example, Lauseker et al analyzed the survival of CML patients in different settings, showing superior survival for patients treated in teaching hospitals [24]. This is of special Fig.…”
Section: Discussionmentioning
confidence: 99%